Legitimacy in International Law; Functions and Elements (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the context of international law and international institutions, legitimacy as a concept has received a considerable amount of attention from scholars as well as political players on a global scale. This is while the issue remains as ambiguous and un-scrutinized as legitimacy has been used/abused based on context, which has led to recent confusions and inconsistency. This article endeavors to create a better understanding upon the matter of legitimacy as a concept by providing definitions and introducing various relevant means as well as provision of insights regarding the usage of the term within the borders of international law. As the topic remains a complex matter, this paper uses most relevant and recent scholarly works of this field to shine light upon the concept of legitimacy within international law. Issues, processes, aspects, functions and elements of legitimacy have been noted throughout this paper in terms of international context to further provide a comprehensive information regarding the state of legitimacy in modern world. Uncertainty remains an issue in this context as there is no consensus in the international atmosphere of law and governing bodies. Thus, this article emphasizes on providing clear information of how various factors have led to this complex state. International lawyers have shown an interest in the recent years regarding legitimacy and this may be of aid for further clarification of effects and relevant elements. Thus, increased participation of such actors on international scale is encouraged for provision of consensus in terms of legitimacy and surrounding debates and ambiguities